EXPLORING PARENTAL INVOLVEMENT OF THE SEA-GYPSY TRIBE IN THEIR CHILDREN’S ENGLISH LANGUAGE EDUCATION - Dunifa, La (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
This study examines the involvement of the Sea-Gypsies tribe in their children’s English education and the factors influencing their participation. The research is guided by two questions: "To what extent are the Sea-Gypsies involved in their children’s English education?" and "What motivates or discourages parents from participating in their children’s English education?" Employing a qualitative microethnographic design, the study was conducted in the Samabahari Village, Wakatobi Regency, a rural and underdeveloped area in Indonesia. The study involved 45 participants, including 20 students, 24 parents, and one English teacher. Data collection methods included in-depth interviews, observations, documents, and visual materials. The data analysis process encompassed familiarization with the data, creating initial codes, collating codes, grouping codes into themes, reviewing and revising themes, and narrating the findings. The results indicate that most parents support their children’s English learning. This support is rooted in three main beliefs: (1) English proficiency will facilitate their children’s pursuit of higher education; (2) speaking English will enhance their children’s job prospects; and (3) the ability to communicate with foreigners is advantageous.